PERKIRAAN DAMPAK KRISIS KEUANGAN TERHADAP EKONOMI, KHUSUSNYA SEKTOR PERTANIAN DAN AGRIBISNIS DI INDONESIA - TAMBUNAN, MANGARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Beginning from the monetary crisis of Bath-Thailand, then gradually to spread to south-east Asia Countries and finally has been Indonesia monetary crisis started the third week in July 1997. Monetary crisis this time to indicate that Indonesia economics more and more open and integrated with world economics. Really Indonesia to face three kind crisis i.e.: (1) Exchange rate crisis where depreciation of rupiah value toward dollars, (2) foreign debt crisis in big quantity, which made by private and government, and (3) probably so infected by diminishing expectation of the community toward various of economics and financial institutions To measure the impact of monetary crisis toward quantitatively economics can be not acted now yet. What that can be acted is to expect its impacts toward economics, especially to agriculture or agribusiness sectors. For need of this research-collected macroeconomics data in the last time that sources from secondary data, processed and analyzed. Because this research especially to expect the impact of monetary crisis toward agriculture or agribusiness sectors, so the agriculture data collected, processed and analyzed detailer. The result of analysis to indicate that monetary crisis in Indonesia that indicated by has been weak of rupiah value to dollars, has impact toward agriculture or agribusiness sectors. Yet, impact intensity depend on: (1) sources of raw material (domestic or foreign), (2) structure of output marketing for domestic or international, and (3) structure of capital, equity and firm portfolio of agribusiness mentioned. Viewed from costly structure and return, so portion of import of input and export of output in agriculture sector significantly to influence toward performance of agriculture or agribusiness sectors. For the agriculture or agribusiness firms that using domestic raw material in theirs production process, monetary crisis maybe not influence so big, if mostly theirs output exported, this crisis will positive impact. Yet, if agriculture or agribusiness firms using raw material from foreign in its production process (example cotton), monetary crisis has influence toward costs structure (increase the cost of input and output per unit) to be bigger. If theirs output market for domestic, so will be gloomier. In this condition, monetary crisis has negative influence toward performance of agribusiness mentioned. Result of the monetary crisis, need be acted a reevaluation to measure rate of return (ROI) investment in agriculture sector. In the last time ROR in agriculture sector only range 15 percent. Not impossible if this monetary crisis has made the populace agriculture is not interesting for investor.
Keywords: Monetary Crisis, Economics Impact, Agriculture and Agribusiness Sectors.